Suspected recurrence of brain metastases after focused high dose radiotherapy: can [18F]FET- PET overcome diagnostic uncertainties?. Issue 1 (December 2016) - Romagna, Alexander; Unterrainer, Marcus; Schmid-Tannwald, Christine; Brendel, Matthias; Tonn, Jörg-Christian; Nachbichler, Silke; Muacevic, Alexander; Bartenstein, Peter; Kreth, Friedrich-Wilhelm; Albert, Nathalie
Abstract Background After focused high dose radiotherapy of brain metastases, differentiation between tumor recurrence and radiation-induced lesions by conventional MRI is challenging. This study investigates the usefulness of dynamicO -(2-18 F-Fluoroethyl)-L-Tyrosine positron emission tomography (18 F-FET PET) in patients with MRI-based suspicion of tumor recurrence after focused high dose radiotherapy of brain metastases. Methods Twenty-two patients with 34 brain metastases (median age 61.9 years) were included. Due to follow-up scan evaluations after repeated treatment in a subset of patients, a total of 50 lesions with MRI-based suspicion of tumor recurrence after focused high dose radiotherapy could be evaluated.18 F-FET PET analysis included the assessment of maximum and mean tumor-to-background ratio (TBRmax and TBRmean ) and analysis of time-activity-curves (TAC; increasing vs. decreasing) including minimal time-to-peak (TTPmin ). PET parameters were correlated with histological findings and radiological-clinical follow-up evaluation. Results Tumor recurrence was found in 21/50 cases (15/21 verified by histology, 6/21 by radiological-clinical follow-up) and radiation-induced changes in 29/50 cases (5/29 verified by histology, 24/29 by radiological-clinical follow-up). Median clinical-radiological follow-up was 28.3 months (range 4.2–99.1 months).18 F-FET uptake was higher in tumor recurrence compared to radiation-induced changes (TBRmax 2.9 vs. 2.0, p < 0.001; TBRmean 2.2 vs. 1.7, p < 0.001). Receiver-operating-characteristic (ROC) curve analysis revealed optimal cut-off values of 2.15 for TBRmax and 1.95 for TBRmean (sensitivity 86 %, specificity 79 %). Increasing TACs and long TTPmin were associated with radiation-induced changes, decreasing TACs with tumor recurrence (p = 0.01). By combination of TBR and TACs, sensitivity and specificity could be increased to 93 and 84 %. Conclusions In patients with MRI-suspected tumor recurrence after focused high dose radiotherapy, 18 F-FET PET has a high sensitivity and specificity for the differentiation of vital tumor tissue and radiation-induced lesions.